2017
DOI: 10.1021/acs.jced.6b00458
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Difference between Protocatechualdehyde and p-Hydroxybenzaldehyde in Aqueous Sodium Chloride Solutions

Abstract: The enthalpies of dilution of protocatechualdehyde and p-hydroxybenzaldehyde in the aqueous sodium chloride solutions were measured by using a mixing-flow microcalorimeter at 298.15 K. Densities of the ternary homogeneous systems at different temperatures (293.15, 298.15, 303.15, 308.15, and 313.15 K) were also measured with a quartz vibrating-tube densimeter. The homogeneous enthalpic interaction coefficients (h 2, h 3, and h 4) were calculated according to the excess enthalpy concept based on the calorimetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…Second, the data presented in Table show that the values of both V ϕ 0 and Δ trs V ϕ 0 are positive in the research systems, which indicates that the hydrogen bond interactions (d) between the hydrophilic sites of the nicotinic acid molecule and the hydroxyl groups of carbohydrates dominate the overall solute–solvent interaction processes in the ternary systems investigated in this study . Notably, similar results were also observed by Pandit et al .…”
Section: Results and Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Second, the data presented in Table show that the values of both V ϕ 0 and Δ trs V ϕ 0 are positive in the research systems, which indicates that the hydrogen bond interactions (d) between the hydrophilic sites of the nicotinic acid molecule and the hydroxyl groups of carbohydrates dominate the overall solute–solvent interaction processes in the ternary systems investigated in this study . Notably, similar results were also observed by Pandit et al .…”
Section: Results and Discussionsupporting
confidence: 88%
“…Second, the data presented in Table 4 show that the values of both V ϕ 0 and Δ trs V ϕ 0 are positive in the research systems, which indicates that the hydrogen bond interactions (d) between the hydrophilic sites of the nicotinic acid molecule and the hydroxyl groups of carbohydrates dominate the overall solute−solvent interaction processes in the ternary systems investigated in this study. 4 Notably, similar results were also observed by Pandit et al 29 for nicotinic acid in aqueous sodium malonate solutions and by Tyunina et al 23 for nicotinic acid in aqueous amino acid buffer solutions, wherein V ϕ 0 and Δ trs V ϕ 0 values were positive. Third, the study shows that in the aqueous solutions of carbohydrate with the same molality and at the same temperature, the values of both V ϕ 0 and Δ trs V ϕ 0 in L-arabinose solution are greater than those in D-xylose solution; however, the S v value is smaller than that in D-xylose solution.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The densities of binary solutions (ethanol + water and 1-propanol + water) and ternary solutions (FA + ethanol + water and FA + 1-propanol + water) were measured at different temperatures (293.15, 298.15, 303.15, 308.15, and 313.15 K) and atmospheric pressure with a precision of 1 × 10 –6 g·cm –3 on an Anton Paar DMA 5000 M digital constant temperature liquid densimeter with automatic temperature control with a standard uncertainty of 0.01 K. The instrument is calibrated annually using dry air and the standard liquid supplied by the manufacturer, according to the manufacturer recommendations. Before each measurement, air and water density checks at atmospheric pressure using dry air and freshly prepared double distilled water were also performed to confirm that the measurement precision did not decrease over the measurement period. ,, All density measurements were performed in triplicate, and corresponding average values were calculated. The standard uncertainty in measured density values was estimated to be 5 × 10 –4 g·cm –3 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the prevention and treatment of cancer is one major concern of the modern society . Cancer chemoprevention using dietary phytochemicals is an effective strategy to reduce cancer incidence rate and mortality and has attracted extensive attention. Moreover, numerous studies have reported that phenolic compounds that are commonly found in fruits, vegetables, and nuts exhibit anticancer and immunomodulatory effects. , …”
Section: Introductionmentioning
confidence: 99%